Factors influencing the utilisation of Youth Friendly Health Services in Blantyre, Malawi - Grace C. Sibande; Rakgadi G. Malapela (AOSIS, 2024)
Background: Usage of Youth Friendly Health Services (YFHSs) remains unsatisfactory in sub-Saharan Africa despite global agreements on the utilisation of these services among the youths. Aim: The aim of the study was to identify factors that influence the utilisation of YFHSs in Blantyre, Malawi. Setting: Four health centres in Blantyre, Malawi. Methods: A descriptive quantitative research design using multistage sampling was used to randomly sample (N = 293) unmarried youths and collect data using a structured questionnaire. Data were analysed using a computerised statistical package for social sciences (SPSS) version 26. Chi-square (χ²) was used to test the significance of the association between variables, and the p-value (p  0.05) was considered significant. Regression analysis was used to examine the influence of independent variables on the utilisation of the services. Results: Less than half of the respondents have ever accessed YFHSs (43%). The Chi-square test showed that the following variables had a significant association with utilisation of the services (p  0.05): gender, age, knowledge, signage, printed health education materials, provider attitudes and being shy or fear of being seen at the services. Conclusion: Age, knowledge, signpost, printed health education materials, provider attitudes and being shy or fear of being seen at the YFHSs are factors that influenced the utilisation of the services. Working on these factors would help to increase utilisation. Contribution: The study findings will help to fill the gap in the provision of YFHSs and thus increase utilisation of the services.